THE CAPABILITY OF STUDENTS PACKET B IN MASTERING READING SKILLS AT Society Learning Center (Pusat Kegiatan Belajar Masyarakat) "PIONEER" - WINDARTI, WINDARTI (2010)
This study attempts to know the capability of the students of Packet B in mastering reading skills and to describe the problems faced by the students in mastering reading skills. The research was conducted at PKBM "PIONEER" on Jl. Palur , Karanganyar, Surakarta. The writer limits the research for the third year students. This research belongs to qualitative study. The instrument used to collect the data needed in this study is a kind of reading test employing Barrett taxonomy reading skills (for determining good, fair, and poor achievers), guide and an interview guide to know the problems faced by students in mastering reading skills. The results of the study are as follows: (a) there is a hierarchy of comprehension's levels questions used in the test. The students are good in literal, reorganization, and inference but they are poor in evaluation and fair ability in appreciation of reading passage, (b) the student's problems were related with vocabulary knowledge, reading strategies, and time allocation. The writer concludes that: (1) The ability of the students Packet B in mastering reading skills is still far from satisfactory, (2) the problems faced by the students are vocabulary knowledge, reading strategies and time allocation.